Implementation The Implementation of the Population - Aware School Program at Kemala Bhayangkari Elementary School in Reducing the Phenomenon of Early Marriage - Tri Lestari; Enung Hasanah; Achadi Budi Santosa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Early marriage and teenage pregnancies under the age of 20 remain a significant issue in Balikpapan, especially due to their adverse effects on adolescents' reproductive health and future well-being. This study aims to analyze the implementation of the Population-Aware School Program (Sekolah Siaga Kependudukan/SSK) at Kemala Bhayangkari Elementary School as a strategy for preventing early marriage through reproductive health education. The study employed a qualitative case study approach. Data were collected through interviews, observations, and documentation conducted from April to June 2026 involving the principal, the SSK coordinator, and lower- and upper-grade teachers as research participants. Data were analyzed using the Planning, Organizing, Actuating, and Controlling (POAC) management framework and Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the SSK Program is effective through four key managerial actions: leading, communicating, motivating, and coordinating. These strategies demonstrate that early reproductive health education, implemented through structured school programs, enhances students’ awareness and serves as a protective factor against early marriage. This study provides empirical evidence that school-based reproductive health education can contribute to preventing early marriage and offers practical insights for strengthening population education programs in Indonesian elementary schools.